2018
DOI: 10.1111/nep.13055
|View full text |Cite
|
Sign up to set email alerts
|

Simple risk score for prediction of haemorrhagic complications after a percutaneous renal biopsy

Abstract: The risk of major complications after a percutaneous renal biopsy can be assessed by a simple risk score calculated from readily available information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
4
14
2
Order By: Relevance
“…Guided by prior evidence, 1,11,20,[26][27][28][29] we collected data on characteristics that may influence the risk of bleeding including age, platelet count, hemoglobin concentration, kidney size, body mass index (BMI), severity of kidney dysfunction, coagulation status, the type of kidney (native or allograft), comorbidities, number of passes with the biopsy needle, and the indications for biopsy.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Guided by prior evidence, 1,11,20,[26][27][28][29] we collected data on characteristics that may influence the risk of bleeding including age, platelet count, hemoglobin concentration, kidney size, body mass index (BMI), severity of kidney dysfunction, coagulation status, the type of kidney (native or allograft), comorbidities, number of passes with the biopsy needle, and the indications for biopsy.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Peri-nephric hematomas in particular are very common, occurring in between 20–86% of cases depending on the timing and modality of the post-biopsy imaging. 3538 However, while the absence of a hematoma does appear to be associated with a lower risk of major complications, immediate post-biopsy hematomas are not useful in predicting clinically significant bleeding later. 39,40 Arteriovenous fistulae occur in approximately 15% of cases and appear to be more common after allograft biopsies.…”
Section: Safety Of Kidney Biopsies In Akimentioning
confidence: 99%
“…The rates of major complications following percutaneous kidney biopsy range from approximately 2–8% in published series. 38,40,43,44 A large, well done meta-analysis by Corapi et al of studies of post-biopsy bleeding complications identified a number of independent risk factors. These included the use of larger biopsy needles, lower pre-biopsy hemoglobin, higher baseline serum creatinine, and higher pre-biopsy systolic blood pressure.…”
Section: Safety Of Kidney Biopsies In Akimentioning
confidence: 99%
“…has been previously described to be associated with renal hemorrhage. [ 2 , 3 , 7 , 37 , 38 ] The addition of the histologic features associated with a significant risk for major post-biopsy hemorrhage in our study (not previously described), could greatly enhance the sensitivity and specificity of such a risk score. In many centers, PRB is mainly performed as an outpatient procedure with shortening of in-hospital post- procedure surveillance.…”
Section: Discussionmentioning
confidence: 78%
“…formulated a risk score for major bleeding after PRB, which had a good discrimination capacity. [ 37 ] Each of the parameters used by Mejia-Vilet et al . has been previously described to be associated with renal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%